Termination of pregnancy for fetal anomaly: a systematic review of the healthcare experiences and needs of parents - Suzanne Heaney; Mark Tomlinson; Áine Aventin (BMC, 2022)
Abstract Background Improved technology and advances in clinical testing have resulted in increased detection rates of congenital anomalies during pregnancy, resulting in more parents being confronted with the possibility of terminating a pregnancy for this reason. There is a large body of research on the psychological experience and impact of terminating a pregnancy for fetal anomaly. However, there remains a lack of evidence on the holistic healthcare experience of parents in this situation. To develop a comprehensive understanding of the healthcare experiences and needs of parents, this systematic review sought to summarise and appraise the literature on parents' experiences following a termination of pregnancy for fetal anomaly. Review question What are the healthcare experiences and needs of parents who undergo a termination of pregnancy following an antenatal diagnosis of a fetal anomaly? Methods A systematic review was undertaken with searches completed across six multi-disciplinary electronic databases (Medline, Embase, PsycINFO, CINAHL, Web of Science, and Cochrane). Eligible articles were qualitative, quantitative or mixed methods studies, published between January 2010 and August 2021, reporting the results of primary data on the healthcare experiences or healthcare needs in relation to termination of pregnancy for fetal anomaly for either, or both parents. Findings were synthesised using Thematic Analysis. Results A total of 30 articles were selected for inclusion in this review of which 24 were qualitative, five quantitative and one mixed-methods. Five overarching themes emerged from the synthesis of findings: (1) Contextual impact on access to and perception of care, (2) Organisation of care, (3) Information to inform decision making, (4) Compassionate care, and (5) Partner experience. Conclusion Compassionate healthcare professionals who provide non-judgemental and sensitive care can impact positively on parents' satisfaction with the care they receive. A well organised and co-ordinated healthcare system is needed to provide an effective and high-quality service. Trial Registration: PROSPERO registration number: CRD42020175970 .